Assessing Performance of Small‐Scale Pumped Irrigation Systems in sub‐Saharan Africa: Evidence from a Systematic Review†. (16th March 2016) - Kamwamba‐Mtethiwa, Jean; Weatherhead, Keith; Knox, Jerry
Abstract: Small‐scale irrigation (SSI) has significant potential to increase crop productivity in sub‐Saharan Africa (SSA). Pumped irrigation systems are one of the technologies increasingly being used by smallholder farmers. The aim of this study was to systematically review evidence on the performance of SSI pumped systems, including motorized, treadle, rope and washer, solar and wind pumps. The study revealed a lack of standardization and use of a wide range of indicators to assess performance. Most evidence related to motorized pumps, and these studies confirmed mixed levels of performance; studies relating to other types of pumped system mostly reported a positive impact, although the method of assessment used was critical. Studies reporting positive impacts tended to be those that used socio‐economic based factors such as yield and profitability, whereas studies reporting mixed performance tended to be those that relied more on technically based indicators such as pumping and irrigation system efficiency. The analysis highlights the sensitivity of interpreting findings from different studies, and how caution should be exercised when comparing performance within and between different types of irrigation systems. The implications for supporting policy development and identifying future research gaps are discussed. Copyright © 2016 John Wiley & Sons, Ltd. Copyright © 2016 John Wiley & Sons, Ltd.